Thermal decomposition of b-cyclodextrin and its inclusion complex with vitamin E - Burkeev, M.; Fazylov, S.; Bakirova, R.; Iskineyeva, A.; Sarsenbekova, A.; Tazhbaev, E.; Davrenbekov, S. (Mendeleev Commun, 2021)
Thermogravimetric kinetic investigation of b-cyclodextrin and its inclusion complex with vitamin E has been carried out. The activation energy and pre-exponential factor of their thermal decomposition have been determined based on the kinetic analysis methods known as the Freeman–Carroll, Sharp–Wentworth, Achar and Coats–Redfern ones.
Keywords: dynamic thermogravimetry; cyclodextrin; pre-exponential factor; thermal analysis; thermal destruction; activation energy